Mn/carbon sphere catalyst for heterogeneous activation of peroxymonosulfate for methylen blue removal - Yusnimar Yusnimar; Khairat Khairat; Chairul Chairul; Silvia Reni Yenti; Wisrayetti Wisrayetti; Barata Aditya Prawiranegara; Heni Sugesti; Panca Setia Utama; Edy Saputra (CHEMICA: Jurnal Teknik Kimia, 2021)
One of the latest innovations in textile waste treatment is advanced oxidation processes (AOPs) methods using an oxidizing agent capable of producing sulfate radicals (SO4•). This study aims to determine the activity of the Mn/Carbon sphere catalyst in the oxidation process, reduce the dye content by using a combination of peroxymonosulfate (PMS) and Mn/Carbon sphere catalyst as an oxidizing agent, and determine the optimum conditions in the process of reducing dye levels in the water. A hydrothermal process carried out the catalyst synthesis process to produce black carbon from D-glucose solution, then impregnated with variations of 3% and 5% of Mn metal. The degradation of methylene blue (artificial waste) of 25mg/L (1:10 dilution) was carried out for 120 minutes with variations in the catalyst mass of 0.001, 0.002, 0.003, and 0.004g and the mass of PMS 0.01, 0.02, 0.03, and 0, 04g in 100ml sample. Mn/Carbon sphere catalyst was able to activate PMS and was able to degrade methylene blue by 88.16%. The optimum condition for reducing the methylene blue levels in the water is at a concentration of 1g/L PMS and a Mn/Carbon sphere catalyst (5% Mn metal) 0.5g/L with an efficiency of 88.16%.